Peningkatan Hasil Belajar Materi Ajaran Sosial Gereja Melalui Problem Based Learning di Kelas XI MIPA 2 SMA Negeri 1 Sintang - Robertus Jematu; Yusmanto Yusmanto (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
This research aims to determine and improve learning outcomes for Catholic Religious Education on Church Social Teaching material. This type of research is a classroom action research (PTK) developed by Hopkins. This research was carried out in two cycles, each consisting of four stages, namely planning, action, observation and reflection. The research subjects were 24 students in class XI MIPA 2 SMA Negeri 1 Sintang. The data collection instruments used in this research were test questions, observation guidelines, and questionnaires. The data obtained is presented in quantitative and qualitative descriptive form. The learning outcomes examined in this research include three dimensions, namely cognitive, affective and psychomotor. The results of the research in cycle I showed that student learning outcomes improved. Based on data analysis, the increase in learning outcomes in cycle I in the academic aspect was 30.33%, the attitude aspect was 16.67%, and the skills aspect was 66.67%. The results of the research in cycle II indicated an increase in student learning outcomes. Based on data analysis, the increase in learning outcomes in cycle II in the academic aspect was 45.84%, the attitude aspect was 83.33%, and the skills aspect was 91.67%. This learning model's implication is that students can become more sensitive to social problems in everyday life and learn to solve them based on Christian ethics and morals.